Critical Role of Exogenous Nitric Oxide in ROCK Activity in Vascular Smooth Muscle Cells - Maruhashi, Tatsuya (Public Library of Science, 2014)
OBJECTIVE: Rho-associated kinase (ROCK) signaling pathway has been shown to mediate various cellular functions including cell proliferation, migration, adhesion, apoptosis, and contraction, all of which may be involved in pathogenesis of atherosclerosis. Endogenous nitric oxide (NO) is well known to have an anti-atherosclerotic effect, whereas the exogenous NO-mediated cardiovascular effect still remains controversial. The purpose of this study was to evaluate the effect of exogenous NO on ROCK activity in vascular smooth muscle cells (VSMCs) in vitro and in vivo. METHODS: VSMCs migration was evaluated using a modified Boyden chamber assay. ROCK activities were measured by Western blot analysis in murine and human VSMCs and aorta of mice treated with or without angiotensin II (Ang II) and/or sodium nitroprusside (SNP), an NO donor. RESULTS: Co-treatment with SNP inhibited the Ang II-induced cell migration and increases in ROCK activity in murine and human VSMCs. Similarly, the increased ROCK activity 2 weeks after Ang II infusion in the mouse aorta was substantially inhibited by subcutaneous injection of SNP. CONCLUSIONS: These findings suggest that administration of exogenous NO can inhibit ROCK activity in VSMCs in vitro and in vivo.